68Ga-DOTA-peptide PET/CT for radiotherapy planning and evaluating treatment response in the management of meningiomas - Sharjeel Usmani; Anjali Jain; Syed Furqan Hashmi; Layth Mula-Hussain; Khulood Al Riyami; Sofiullah Abubakar; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2023)
Meningiomas overexpress somatostatin receptors (SSTR). PET imaging with SSTR ligands such as 68Ga-DOTA-peptide has recently shown high diagnostic accuracy in identification of meningiomas due to lack of normal bone and brain activity. PET-derived parameters, especially gross tumour volume (GTV) delineation improves inter-observer variability and appears to be particularly promising for RT planning. The potential strength of 68Ga-DOTA in the ongoing assessment of treatment response and disease progression in meningioma, particularly in the post-surgical and post-radiation settings is encouraging. More prospective randomized studies with large cohorts of patients are required to define the effective role of this modality. Keywords: 68Ga-DOTA PET/CT; Meningioma; 177Lu-DOTATATE; PET/CT; radiotherapy planning.